Research on Intelligent Shelves Based on RFID Technology - Wang, Mintao; Li, Pengfei (Journal of Artificial Intelligence and Information, 2025)
Intelligent shelves are the foundation of intelligent warehouse system management. As an intelligent storage management technology application, RFID technology can achieve efficient and precise management of material shipment, logistics, warehousing, stacking, inventory and outbound through wireless radio frequency identification communication.With the continuous maturity of technology, at present, it is the opportunity for traditional warehousing enterprises to transform into intelligent warehousing enterprises. The application and development of intelligent shelves will also be a hot spot in the fierce competition of the warehousing industry.With the development of industrial automation and intelligence, the research and application of intelligent shelf technology is urgently needed.This article analyzes the communication principles and advantages of RFID systems, as well as the technological research in intelligent shelves, with the hope of further improving the application level of RFID technology and promoting the intelligent development of warehousing systems.